2006
DOI: 10.1111/j.1600-0404.2005.00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary factors and smoking as risk factors for PD in a rural population in China: a nested case-control study

Abstract: Among 16,488 subjects surveyed, we diagnosed 464 subjects with PD. Then, four sex- and age-matched controls were paired with each definite PD case. A total of 85 cases and 340 controls were analyzed. Meat consumption and the body mass index (BMI) were inversely associated with PD. The PD risk declined with the increment of BMI. A history of gastric ulcer was associated with an increased risk of PD. As to smoking, there seemed an increased risk of PD among individuals who smoked regularly, non-significantly. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…A Swedish case-control study reported inverse associations of PD with intake of meat and ham, eggs, and wheat bread [295]. An inverse association between intake of meat and PD was also found in a Chinese case-control study nested within a nutrition intervention trial [466], but this study reported no associations of PD with intake of eggs, fruits, or vegetables and PD.…”
Section: Specific Food Itemsmentioning
confidence: 56%
See 3 more Smart Citations
“…A Swedish case-control study reported inverse associations of PD with intake of meat and ham, eggs, and wheat bread [295]. An inverse association between intake of meat and PD was also found in a Chinese case-control study nested within a nutrition intervention trial [466], but this study reported no associations of PD with intake of eggs, fruits, or vegetables and PD.…”
Section: Specific Food Itemsmentioning
confidence: 56%
“…An early case-control study [127] reported higher frequency of hypertension among PD cases compared to controls, although no p value was provided. Six other case-control studies [132,142,303,358,409,466] found no association between selfreported hypertension and PD, one study found lower risk of PD associated with hypertension in univariate analyses, but when adjusting for smoking and other variables, the association did not persist [631]. Another case-control study reported increased PD risk associated with hypertension in women (OR 1.62, 95% CI 1.00-2.62) but not in men [540].…”
Section: Vascular Diseasesmentioning
confidence: 96%
See 2 more Smart Citations
“…The Western dietary pattern has been shown to be significantly associated with high plasma homocysteine and inflammatory biomarkers in the HPFS and NHS (17,18). However, in some case-control studies individuals with PD had significantly lower intakes of meat and eggs than did controls (45,46). A greater intake of red meats or processed meats, which are major dietary sources of purine, has been reported to be associated with higher plasma uric acid concentrations (47).…”
Section: Discussionmentioning
confidence: 99%